The Development of Neuromuscular Performance and Its Effect on Reducing Injuries in Swimming Sports for Female Students of Physical Education and Sports Science - Hameed Kzar Al_ Masoodi , Fatimah; Sabah Mohammed Al_Khfaji, Wafaa (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to create a program to develop neuromuscular performance and know its effect in reducing injuries in swimming among female students of physical education and sports science. The research sample was randomly chosen from students of the College of Physical Education and Sports. The science and the research sample included 40 students, and among the researchers, the experimental method was used, and the researcher concluded that the program has a significant impact on some of the interoperability capabilities of students and training of neuromuscular performance has a positive effect on the reduction of some injuries in swimming sports is the most common among students of the Faculty of Physical Education and Sports Science.